CONTRIBUCIÓN AL ESTUDIO DE LA PRESIÓN INTRAOCULAR NORMAL EN CANINOS MESTIZOS MEDIANTE LA TÉCNICA DE LA TONOMETRÍA - Hinostroza M., C. Elizabeth (2003)
Normal intraocular pressure in mongrel dogs (Canis familiaris) was determined by the tonometry technique. A total of 60 healthy dogs between 1 to 4 years old were selected (30 males and 30 females). The results obtained with the Shiotz tonometer revealed that the values of intraocular pressure were 24.10 ± 1.02 and 24.30 ± 1.09 mm Hg for the right and left eye, respectively. No significative differences were found between right and left eye, or sexes. However, in males the right eye had a higher (P<0.05) intraocular pressure (26.48 + 1.27) than the left eye (20.15 + 1.59 mm Hg) .